"Inharmonious Elements" and "Racial Homogeneity": New England Exceptionalism and Immigration Restriction. Issue 3 (3rd July 2021) - Arnold-Lourie, Christine
Abstract : From the colonial period, many Americans have adhered to the notion of the United States as a unique nation, rooted in the idealism of the Pilgrims and Puritans, and deriving its values, purpose, and meaning from its Protestant, Anglo-Saxon heritage. The belief in New England exceptionalism as the source of American greatness provided a foundational past that scientists, academics, and legislators invoked in the twentieth century to justify laws restricting the arrival of Asians, Catholics, and Jews. These laws reflected historical tensions over American identity and reverberate in the nation's ongoing attempts to define and comprehend a shared past,